Sea-Level Rise and Related Potential Hazards on the Argentine Coast - Lanfredi, Néstor W. (1998)
Fil: Lanfredi, Néstor W.. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina